Pengaruh Kampanye “Semua Ada Di Shopee” Terhadap Tingkat Kepercayaan Pengguna E-Commerce Di Tangerang Selatan - Nayla Nurially Sofyan; Nabila Kanaya Winata; Sadiyah El Adawiyah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the influence of the "Everything is on Shopee" campaign on user trust levels in South Tangerang. Using explanatory quantitative methods, this study collected data from 30-100 respondents through a structured questionnaire. The results indicate that the campaign has a significant influence on building user trust through the dimensions of message clarity and frequency of exposure. Key findings revealed that respondents had a high level of agreement regarding transaction security and Shopee's system reliability as a result of the campaign's consistent messaging. This study recommends Shopee continue to maintain the credibility of product information to maintain user loyalty in urban areas.